Hidroksiapatit (HAp) dari Cangkang Kerang Mutiara Air Tawar (Kijing)(Anodonta woodiana) Rawa Pening Kabupaten Semarang - Agung Rimayanto Gintu (Jurnal Migasian, 2022)
Hydroxyapatite (HAp) was one of biomaterials for hard tissues reparation synthesized from Molluscan shells. In this study treated the synthesis of HAp from Anodonta woodiana clams shells obtained from Rawa Pening Lake, Semarang regency, Central of Java. Physicochemical characterizationsagainst the shells showed Ash contains 0,9985 ± 0,0005g/g; Calcium / CaO 0,4460 ± 0,0082g/g; Calcium / CaCO3 0,1845 ± 0,0012g/g; and Phosphate 0,1893 ± 0,0102g/g, suitable with the need in HAp synthesic. HAp in this study synthesized by Base Precipitation method and obtained rendement of synthesis 50,25 ± 0,0384% and HAp with Ratio Ca/P 1,4611% based on Bray and 1,3847% by Olsen’s methods; Porosity 50,25 ± 0,0384%; Biodegradability 70,22 ± 0,0203%; Swelling ability 65,28 ± 0,0291%; Density 0,8898 ± 0,0008g/mL; Kinetic Viscosity 1,1986 ± 0,0982CTs; and Mollecular Weight 0,0076 ± 0,0007g/mol. Based on the results concluded that HAp success synthesized from A. woodiana clams shells by Base Precipitation methods.